Heat transfer enhancement in a triangular duct using compound nanofluids and turbulators - Ahmed H.E.; Ahmed M.I.; Yusoff M.Z. (Elsevier Ltd, 2023)
Ducts; Flow of fluids; Heat transfer; Heat transfer coefficients; Vortex flow; Vorticity; Distilled water; Experimental investigations; Heat Transfer enhancement; High gradient; Laminar heat transfer; Nanofluids; Vortex generators; Wall temperatures; Nanofluidics